Diseño, construcción y puesta a punto de un prototipo de sistema electromecánico construido con herramientas didáctico-pedagógicas lego education compatibles con la fábrica didáctica de la UAN sede sur (2020)
This current project includes the design, construction and presents to a point the electromechanic-didactic system for the selection of general products of a line of production. The prototype is in the capacity of identifying a prominent box from a specific location; manipulate the selected box through a robotic arm and then locating it in a specific location. Once located, the parameters of design from the electromechanical system and keeping in mind the dynamic analysis stablished with the mentioned purpose, it was proceeded to the design and then structural construction of the dispositive. Equally, the construction activities and evaluations of the functioning of the dispositive were done by making use of the tools didactic/pedagogic LEGO education programmed with the specialized software MindStomra EV3, uniquely by the brand, for the automatization and control of the robotic-dispositives. The mentioned didactic-pedagogic tools from the LEGO education brand match with the working kits of the “Didactic Factory” from south headquarters of Antonio Nariño University which have the potential to cover a wide range of especialized excercises aplicable to Electromechanic engineering and its cognitive fundamentals.